Um ensaio educacional na Casa da Esperança: tentativas de estabilizar o instável no autismo - Lima Neto, Felipe Franklin de (2006)
This work cuts the thematic one of the autism through the concepts of Difference in Gilles Deleuze, of Relations know-power, Genealogy, Disciplines and Normalization in Michel Foucault and of Imitation and Invention gifts in the workmanship of Gabriel Tarde. Inquiry the process of subjection of eight probationary pupils of the House of the Hope. This institution, headquartered in the city of Fortaleza (Ce), is considered international reference in the clinical and educational boarding of autistas. The central hypothesis that guides our inquiry is of that the subjectivity of these probationary pupils results of multiple enrolled unfoldings in the relations of diagnosis, verified and analyzed learning and inclusion to the long one of the research. Methodological we support ourselves in the reflections of sociologist and interacionist-symbolic Howard Becker. In special, its microsocial vision concerning the improvisation and of the versatility with which a researcher must use itself in the multiple situations where interacts with its searched citizens. Being a research of qualitative nature, we carry through bibliographical surveys on the subject, open and half-direct interviews and filmings with the searched citizens and national and international specialists, participant comment, collection of informal stories, reports of professors of the probationary pupils, handbooks, visits the institutions and schools of the public and private net that they deal with autists in the similar Ceará, participation in forums, seminaries and meeting on autism and subjects, research in the InterNet, beyond a systematic consultation in the medias of mass (periodicals, specialized magazines of great circulation and, films and sets of documents). Our work if structure at four moments. In the first one of them, we configure the autism while a subject that "appeared" and if develops under the sign of the controversy. We still demonstrate that enrolled to the conceptual mutations of the autism in the great classification systems such as the ICD-10 and the DSM-IV possesss linkings with the involved scientific beliefs in the "sprouting of the autism" and with the development of specialized areas such as Genetic Engineering and the Neurosciences. Through the concepts of imitation and invention in Gabriel Tarde we analyze what it feeds these great quarrels to the light of the daily one of the anonymous and common people. At as a moment, we complement our conceptual instrumental through the concept of Difference in Gilles Deleuze and of the concepts of Relations know-power, Genealogy, It disciplines and Normalization in Michel Foucault. Our intention is to probably certain slight knowledge that frame the autism as a complicated subject, difficult, enigmatic and normalized.- At the third moment, we funnel the quarrel of the two previous chapters addressing in our specific question of research. At this moment we approach as it operates the educational concept of Natural Functional Resume ahead created by Judith LeBlanc of the reformularizations that the Behaviorism of skinnerian basis considered by Casa da Esperança in it processed. We still analyze the pedagogical proposals of the protecting workshops where the searched citizens were and/or had been monitorial. In the room and last moment of the work, we map the citizens searched from the effect that the normalization power (Foucault) produces in the subjectivity of the "pupils special of Casa da Esperança". In the final consideration, we converge the quarrel effected in the three chapters evidencing the effect of the relations of diagnosis, learning and inclusion in "the searched" production of the subjectivity of and because we consider Casa da Esperança an Island of Inclusion.